An estimation of the Baltic cod stock production - B. Draganik (Acta Ichthyologica et Piscatoria, 1978)
In this paper, the author describes several “simple production models” as formulated by Schaefer (1954), Fox (1970, 1974), and Pella and Tomlinson (1969). On the basis of fishery statistics on Baltic cod the volume of the annual maximum sustained yield was estimated. This volume varies from 145 to 160 thousand tons depending on the model applied.